L’esercizio e gli Essais. La retorica filosofica di Montaigne (ENTHYMEMA, 2012)
The Essais’s writing generates a form of original pyrrhonian philosophical discourse, apt to express the infinite variety of the world. In this way it paves the way to a limitless method of investigation: zetetics.